Fabrication of Direct Compressible Tablets Containing Chatuphalathika Extract Obtained through Microwave-Assisted Extraction: An Optimization Approach - Chaowalit Monton; Piyapa Keawchay; Chantisa Pokkrong; Pariyakorn Kamnoedthapaya; Abhiruj Navabhatra; Jirapornchai Suksaeree; Thaniya Wunnakup; Natawat Chankana; Thanapat Songsak (MDPI AG, 2023)
This research sought to optimize the microwave-assisted extraction of Chatuphalathika as an herbal recipe maximizing the active compounds and the antioxidant activity by the Box-Behnken design. Three factors-microwave power, time, and cycle-were varied. Eight responses-extraction yield, total phenolic content, gallic acid content, corilagin content, chebulagic acid, chebulinic acid, IC50 from DPPH assay, and IC50 from FRAP assay-were monitored. Furthermore, cytotoxicity was evaluated to ensure the safety of the extract. After that, the optimized extract was compressed into tablets. The results showed that the optimal condition of the microwave-assisted extraction gave the simultaneous maximum extraction yield, total phenolic content, and antioxidant activity with a microwave power of 450 W for 30 s and 3 cycles. The extract obtained from the optimal condition exhibited a good safety profile although a concentration of 5 mg/mL was used. The optimized tablets were achieved when a compression force of 1500 psi and magnesium stearate of 1% were applied, and no sodium starch glycolate was added. In conclusion, the optimal green extraction method could be used for the extraction of the Chatuphalathika. Furthermore, the fabrication of Chatuphalathika tablets was successful, as the tablets had low friability with a short disintegration time.